Strategi Keberlanjutan sebagai Wayfinding: Menelusuri Proses Penciptaan Praktik Cerdas (Practical Intelligibility) untuk Ekonomi Regeneratif - Ine Rahmadania Saldianovitta (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2026)
The transition from sustainability that emphasizes negative impact control to a regenerative economy requires organizations to move beyond the linear planning logic that has been dominant in sustainability strategies. However, the literature still does not explain much about how strategic direction is shaped as normative goals get stronger, but the operational path remains open and uncertain. This research aims to synthesize the relationship between wayfinding, practical intelligibility, and sustainability strategies, as well as formulate a conceptual framework for sustainability strategies as wayfinding towards a regenerative economy. This study uses an integrative literature review method of international journal articles for the 2020-2025 period, which is systematically traced in three main domains, namely wayfinding, practical intelligibility, and sustainability-regenerative strategy. The analysis was carried out through a thematic-conceptual synthesis to identify literature developments, common points, and research gaps. The results show that the wayfinding literature has evolved towards adaptive navigation, while the practical intelligibility literature confirms the importance of practical intelligence in recognizing reasonable actions in certain situations. Meanwhile, the literature on sustainability and regenerative strategies shows that organizational transformation takes place in a nonlinear manner, is full of tension, and requires continuous learning. The main finding of this study is that practical intelligibility is a connecting concept that explains how sustainability strategies can be understood as a wayfinding process. Thus, sustainability strategy is more appropriately understood as an adaptive, reflective, and collective orientational practice in shaping the direction towards a regenerative economy